UPDATING THE GEOLOGICAL EXHIBITION AT THE MUSEU EDUCATIVO GAMA D’EÇA, SANTA MARIA, RIO GRANDE DO SUL, BRAZIL - Leal, Andressa Gomes; Lopes, Alyssia Moraes; Nobre, Augusto Gonçalves; Pimentel, Samuel Marim Braga; de Paula, Bernardo Duque; Steffenel, Felipe Barchet (Boletim Paranaense de Geociências, 2025)
The Gama d’Eça Educational Museum is affiliated with the Universidade Federal de Santa Maria (UFSM) and is housed in a historic mansion located in the city center of Santa Maria. Its strategic location and active programming make it a key space for fostering interaction between the university and the broader community. Among the museum’s public engagement strategies is the periodic renewal of long-term exhibitions, particularly those related to applied sciences and everyday life. The year 2025 marks a special occasion for UFSM: the 60th anniversary of its Geography undergraduate courses, which are housed within the Department of Geosciences. This department also maintains the university’s lithotheque, which has partnered with the Gama d’Eça Museum to carry out a revitalization of its mineral and rock exhibition. Scheduled to launch in the second half of 2025, the renewed exhibition will showcase examples of geodiversity through the themes of ferrous metallic ores, non-ferrous metallic ores, non-metallic (or industrial) ores, energy resources, ornamental rocks, and gemstones. The exhibition is expected to attract approximately 8,000 visitors by the end of 2025 and aims to inspire similar ex situ geoconservation initiatives in other institutions.